EBOLA-A DANGER: CLEAR AND PRESENT - Sultan, Shahid; Jadoon, Huma; Haroon, Muhammad Zeeshan (Journal of Ayub Medical College Abbottabad, 2014)
Over the past decade, the public health landscape has changed significantly. The focus of policy makers and donors has shifted from communicable disease to chronic non-communicable diseases owing to it being not only a clear threat to the human health, but also to economic growth and development. But this year Ebola gave us a stark reminder that communicable diseases are still at play and unlike non-communicable diseases can cause devastation globally in matter of months. Ebola has run amok havoc on human health in Western Africa. Ebola is an extremely contagious haemorrhagic virus whose incubation period is very rapid and which, once in the bloodstream, quickly infects many cell types, leading to multi-organ failure, haemorrhage and shock. In its rampage in West Africa, it appears to cause death in up to 70% of those infected. As of 14th November 2014 it has killed up to 5,1601 people and is predicted to kill many more in the months ahead. The virus is transmitted in body fluids, primarily blood, saliva, emesis or stool and does not appear to be transmitted through the air2 but recently, evidence suggests that Ebola might also spread by droplet infection especially in confined spaces.3 The disease not only has a heavy toll on human life but also on the social structure of the society in the worst affected countries. It has killed entire families overnight leaving thousands of children orphaned.4 Currently there is no approved antiviral therapy or vaccines available for its treatment or prevention. During the current outbreak, plasma from convalescent patients have been used with some success in treating Ebola patients.5 Ebola is not a new virus. It was discovered by Peter Piot in 19766 during the first outbreak on the banks of river Ebola. One might think that our knowledge of diseases, its spread and control would have grown since its discovery and subsequent outbreaks, but looking at the current epidemic, it is clear that not much has been learned. Ebola has been depicted as an exotic virus and misrepresented as incurable and 99% fatal, leading to hasty renunciation into its spread and control. Initially Ebola spread was blocked by rapid responses by heroic health teams in the remotest areas of centralAfrica. As it has found its way into crowded slums and broken health systems, number of new infections and subsequent deaths have increased so dramatically that very few experts are willing publicly to predict how many more may succumb to this disease. Ebola because of its high mortality, rapid transmission, high fatality and rapid spread in urbanized areas resulted in a perfect storm of condition which led this outbreak to reach to an epidemic proportion. Ebola prospers on poverty, failed health systems and collapsed societies that cannot protect themselves. West Africans countries which are currently worst affected by the epidemic, are unable to muster the resources required to control this disease. These countries do not have the means to enforce containment procedures to the optimal extent. Health work force is struggling to treat existing Ebola patients - a force, i.e., inadequate in numbers and poorly trained as is fashionable in these countries. Resultantly, each week hundreds of new cases are seeking treatment. Overburdened health service delivery centres are turning away patients, who then go on to infect others. Organizations with technical expertise, legal powers and resources have known about Ebola for many years. Although larger outbreaks of Ebola were predictable yet very little was done to prevent or prepare for it. Previous Ebola outbreaks had affected just a few hundred people and that too were confined to Africa.7 Developed countries and people or industries that could make a difference were complacent primarily because Ebola was largely confined to the jungles ofAfrica which kept them out of the line of fire. The valiant efforts of few medics who ventured to control and treat it permitted a further level of complacency. Now that complacency is shattered. The Western governments are getting involved. The donors are moving in. The WHO is vocal. The developing interest and fear over Ebola seems to be a good omen for the world. This disease by any means is a horrifying prospect but what is most important is that in many respects this disease and the threat it poses are completely unnecessary. Ebola is a hypochondriac’s nightmare. Malaria kills more in a day than Ebola has in months. Chances of contracting tuberculosis and dying from it are far more than getting Ebola. Panic coupled with failed health systems and myths surrounding the disease have caused far more devastation than what this disease could have achieved on its own. In the wake of Ebola outbreak, routine health care has collapsed. Both health care providers and patients are avoiding health care facilities for fear of infection. As a result, tens of thousands of people additionally could die from treatable causes like malaria, acute respiratory tract infections and diarrhoea Despite its deadliness, this disease is very much preventable as long as proper education and public sanitation efforts are enforced to combat it. In this endless stream of destruction inWestern Africa,Nigeriahas managed to clear Ebola from its territory. They managed this somewhat reclusive achievement by adhering to the strict protocols required to bring this infection under control. Carriers were isolated, contacts were traced, and patients were treated in hospital settings specifically equipped with the tools and trained health workers to manage it. Plus they embarked on a massive public education campaign. This feat was achieved not only because ofNigeria’s resolve to control Ebola but also significantly due to the fact thatNigeriahas better infrastructure and health system in place to cope with the outbreak. The very absence of these in the countries at the epicentre of the crisis offers an explanation to the fact why the situation has spiraled out of control. For countries like Pakistanwhere Ebola has not been reported so far8, it does not mean that they are in clear and carry on with their usual way. It is just matter of one or two imported cases and swiftly outbreak will be established with all its devastation. Only by taking a systemic approach and strengthening all components of existing health systems will enable us to tackle and contain the tragic consequences caused by the likes of the Ebola virus. We see that health systems are destroyed in many countries by either poverty, conflict, chronic underfunding or a lack of well-trained and skilled health workers. In addition to what has been mentioned, international health organizations which are widely known for their bureaucracy, infighting, academic perspective and lack of implementation capacity need to improve threat perception and preparedness and have to invest in research on emergent and novel infections. In the case of failure many more lives will be lost.